Exposure to particulate matter upregulates ACE2 and TMPRSS2 expression in the murine lung - Sagawa, Tomoya; Tsujikawa, Takahiro; Honda, Akiko (Elsevier Inc, 2021)
Coronavirus disease (COVID-19) is currently a serious global issue. Epidemiological studies have identified air pollutants, including particulate matter (PM), as a risk factor for COVID-19 infection and severity of illness, in addition to numerous factors such as pre-existing conditions, aging and smoking. However, the mechanisms by which air pollution is involved in the manifestation and/or progression of COVID-19 is still unknown. In this study, we used a mouse model exposed to crude PM, collected by the cyclone method, to evaluate the pulmonary expression of angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine type 2 (TMPRSS2), the two molecules required for the entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) into host cells. Multiplex immunohistochemical analysis revealed that exposure to PM increased the expression of these two molecules at the same site. Furthermore, image cytometry analysis revealed increased expression of these proteins, particularly, in the alveolar type 2 cells and macrophages, which are potential targets for SARSCoV-2. Our findings provide an experimental evidence that exposure to PM may adversely affect the manifestation and progression of COVID-19, mediated by the impact of SARS-CoV-2 on the site of entry. The study results suggest that examining these effects might help to advance our understanding of COVID-19 and aid the development of appropriate social interventions
Keywords: Coronavirus disease; Severe acute respiratory syndrome coronavirus 2; Particulate matter; Angiotensin-converting enzyme 2; Transmembrane protease serine type 2; Natsuko Miyasaka; Michitaka Tanaka; Takashi Kida; ACE: Public Health and Toxicological Research; ACE-PUTOR; University of Port Harcourt